A mechanistic and empirical review of antcins, a new class of phytosterols of formosan fungi origin - Senthil Kumar, K.J.; Gokila Vani, M.; Chen, Chieh-Yin; Hsiao, Wen-Wei; Li, Jing; Lin, Zhan-xi; Chu, Fang-Hua; Yen, Gow-Chin; Wang, Sheng-Yang (Yàowu shi͡p︡in fenxi, 2020)
Antcins are unique phytosterols isolated from A. cinnamomea and A. salmomea, which are the endemic fungus of Taiwan. A. cinnamomea has long been highly valued medicinal mushroom in Taiwan and traditionally used as a folk remedy for various human illness. Recent scientific explorations claimed that the pharmacological activities of A. cinnamomea and A. salmomonea are gone beyond their original usage. The therapeutic efficacy of these medicinal mushrooms was attributed to their high content of unique bioactive secondary metabolites, including terpenoids, benzenoids, ubiquinol derivatives, polysaccharides, lignans, nucleic acids, steroids, and maleic/succinic acid derivatives. Antcins is a group of steroids in Antrodia spp. with ergostane skeleton received much attention in Taiwan's academic circle due to their broad-spectrum of biological activities. At present, twelve antcins, i.e. antcin A, B, C, D, E, F, G, H, I, K, M, and N along with twelve derivatives/epimers (25R/S-antcin A, B, C, H, I and K) and seven analogs (methyl antcinate A, B, G, H, K, L and N) were identified. Several studies have demonstrated that antcins possessed anti-cancer, anti-inflammation, anti-oxidant, anti-diabetic, anti-aging, immunomodulation, hepatoprotection, and hypolipedimic activities. The main goal of this review is to define the chemistry, isolation, advances in production, and biological activities of antcins and their derivatives/analogs. Special attention has been given to a detail view of their biological activities in vitro and in vivo and their pharmacological potentials. [Display omitted] •Antcins are identified as major bioactive constituents of Antrodia cinnamomea.•Antcin-M, methyl antcinate-K and -L were only found in Antrodia salmonea.•Antcins are derived from ergosterol biosynthesis.•Antcins exhibited strong anticancer, antiinflammation and antiaging properties.•Hepatoprotective and anti-cancer effects of antcins are highly investigated.